Discourse on Reporting Political Campaign Funds in Regional Head Elections in Indonesia - Djamal, Samhi Muawan (Pusat Penelitian Ilmu Sosial dan Humaniora Kontemporer, 2022)
In the regional head election discourse, reporting campaign funds is a central issue in realizing democratic practices that comply with the rules. This study aims to discuss the issue of reporting campaign funds in the implementation of regional head elections in Indonesia. Through a qualitative approach with descriptive narratives and the instruments used are interviews with informants who understand the issue of campaign finance reporting, especially in the 2020 regional head election. The use of the campaign finance information system application is considered effective in reporting campaign funds if it is judged by the ease of access, the usefulness of time, and disclosure of information in unraveling the chaotic reporting of campaign funds at every political stage. Although the issue of verification of report data is a concern that needs to be constantly criticized so that related parties can improve the quality of verification according to an open and sustainable procedure.